Exploring the nexus between post-traumatic stress disorder and patriarchy: a gender-based variation - Minahil; Fizza Batool; Amna Noor (Journal of the Pakistan Medical Association, 2024)
Respected Editor, Post-traumatic stress disorder (PTSD) is a psychological disorder resulting from witnessing or experiencing trauma, aggravated by repeated exposure to stress and anxiety. We aim to highlight the underrepresentation of PTSD in a third-world country, its gender-specific variations, and its disproportionate prevalence in women in a male-dominated society. According to recent studies, gender-based differences in PTSD are reported as 2:1, favouring women. Statistics reveal that men face more traumatic incidents, ranging from violence, bloodshed, and natural disasters.1. Yet women are more susceptible to PTSD because men, encountering such occurrences regularly, perceive it as a norm and find it easier to cope with it than their female counterparts, who happen to have a more significant post-trauma recovery time, which may be a result of fluctuating gonadal hormone levels in young females, as hypothesized by recent studies.2 Furthermore, Pimlott-Kubiak’s theory of trauma and PTSD (2003) suggests that patriarchy exacerbates mental health disorders in women as a vast majority of victims of abuse happen to have their spouses as assailants, categorizing as intimate partner violence.3 Being considered a taboo, women who have experienced assault are silenced due to stigmatization. They become a target of victim shaming and are discouraged from discussing the matter. With no therapy, self-blame ensues, along with a wide spectrum of symptoms of PTSD, like borderline personality disorder, flashbacks, eating disorders, disassociation, and depression, forcing the ‘labelled’ women to sever all positive connections and distance themselves from their loved ones due to fear of being judged.4 Complex Chronic PTSD may result from witnessing or experiencing assault since childhood in an abusive household from an aggressive male, which can trigger mental health issues when dealing with life's challenges as adults.5 Failing to find any discussion on this topic in medical research databases including PubMed and PakMediNet, solidifies our point that lack of awareness and research about the adverse effects of patriarchy on the mental health of women living in a developing country leads to a society where negligence prevails, fueling a vicious cycle of psychological disorders, passed on from generation to generation. Being a disorder that haunts victims for life, PTSD should be tackled with awareness, therapies, and emotional support to ensure a healthy life for all women. More research should be conducted to highlight this issue so that people can talk about such concerns more comfortably and the harm caused by PTSD in Pakistani society can be minimized.